(3Mbhb GdEfSGf aj GdVHW GdbVGFj (B/s - (3YHO GdYRjR, YUGe RcQjGs ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI,s, 2011)
(3jJfGhd cJGH (B((3Mbhb GdEfSGf aj GdVHW GdbVGFj(B) (3hGdPj bGe HJCdjag O(B. (3YUGe RcQjG YHO GdYRjR aj MhGdj (B(423) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3Mbhb GdEfSGf(B) (3eSJYQVG GdeMJhjGJ aj GdehVhYGJ GdJGdjI (B: (3Mbhb GdEfSGf aj eUQ, GdMQjGJ GdYGeI, OhQ GdTQWI cSdWI aj GdVHW GdbVGFj, GdbGfhf GdOSJhQj GdeUQj, Mb GdOaGY, Mbhb GdEfSGf aj GdbVGA GdeUQj, UdGMjGJ hegGe GdTQWI aj GdVHW GdbVGFj, bGfhf GdELQGAGJ GdLfGFjI aj eUQ, GdQbGHI GdbVGFjI Ydi CYeGd GdVHW GdbVGFj, Mbhb GdEfSGf aj GdbGfhf GdOhdj(B. s
(3HHdjhLQGajI (B: (3UaMI (B410-419.s
Keywords: (3Mbhb GdEfSGfs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdVHW GdbVGFjs -- (3eUQs